Peran UMKM dalam meningkatkan pertumbuhan ekonomi di Indonesia - Sarif, Reza (Maliki Interdisciplinary Journal, 2023)
In recent decades, the government and economists have prioritized Indonesia’s economic growth. Micro, Small and Medium Enterprises (MSMEs) have become the backbone of the Indonesian economy, contributing a large share of employment and playing a significant role in increasing the country’s GDP. Examining the important role of MSMEs in increasing economic growth in Indonesia is the aim of this research. This study used a qualitative research method with a literature study approach. This study noted a number of positive impacts generated by the MSME sector in the context of economic growth. The results of this study indicate that the role of MSMEs in driving economic growth is quite significant through strengthening the quality of human resources, creating jobs, and implementing digitalization of MSMEs.